Exploring Biological Predictive Factors of Progression After Surgery in High-Risk Renal Cell Carcinoma: Results From the French Cohort of the Randomized S-TRAC Trial Patients - Ouzaid, Idir; Kammerer-Jacquet, Solène Florence; Khene, Zineddine; Ravaud, Alain; Patard, Jean-Jacques; Bensalah, Karim; Rioux-Leclercq, Nathalie (Frontiers in Surgery, 2020)
Objective: We aimed was to explore biological predictive factors of progression after surgery in non-metastatic RCC using the collected tumors in the French cohort of the randomized S-TRAC trial patients. Patients and methods We analyzed the tumors of the French cohort of STRAC that included 44 cases of ccRCC that were collected from 6 centers. The main objective was to explore biological predictive factors of response (defined as PFS) to sunitinib. Aboard spectrum analysis including immunohistochemistry, FISH, CGH-Array, Transcriptomic analyses were performed on the tumors. Results Analysis of vascular density showed type 1 vascular stroma corresponding to high vascular density was associated with progression (p<0.034). loss of PBRM1 (Poly bromo-1) expression showed a distinct profile: a highly histopathological aggressive tumor with a marked angiogenic profile (VEGF overexpression and immature vascular stroma type 2), no PD1 or PDL1 expression and WT status of the VHL gene. There were 27 chromosome regions gained in patients with progression (on chromosomes 7 and 16, and to a lesser extent 8, 12, 17, 17, 19, 20 corresponding to 605 associated genes) and 10 regions lost in these same patients on chromosomes 8 and 9, and to a lesser extent 2 and 21 corresponding to 25 associated genes. Conclusion We found that a angiogenic phenotype defined by a high vascular density with a vascular type 2 stroma was a predictive factor of sunitinib resistance. Regardless of adjuvant treatment, chromosomal gains and losses and genomic alterations including PBRM1 loss were associated with worse outcomes.